Heating simulation of a Li-ion battery cylindrical cell and module with consideration of gas ejection - Yoichi Takagishi; Yasufumi Tozuka; Takumi Yamanaka; Tatsuya Yamaue (Energy Reports, 2022)
A comprehensive 3D heating test simulation model of a Li-ion cylindrical cell and module considering gas flow and combustion was developed. The model was based on the equivalent circuit model and included cell heating (Joule heating and thermal decomposition) gas ejection and flow from the cell, and gas combustion. First, the surface temperature and voltage profiles of a model of a commercial 18650-type cell were validated using an actual heating experiment. Subsequently, a simulated model of the battery module, comprising 98 cells heated by a burner was developed, and the thermal runaway behavior of the module was evaluated. The model facilitated the evaluation of the steps that occurred during heating the battery module until gas ejection, including melting of the housing, shutdown of the separator, and cell-to-cell propagation of the thermal decomposition reactions. Therefore, we believe that this can be a helpful tool for designing battery cells and modules. The models in this study were developed using COMSOL Multiphysics software.